Lower extremity soft tissue defect reconstruction with the serratus anterior flap. Issue 3 (15th October 2013) - Mastroianni, Melissa; Leto Barone, Angelo A.; Shanmugarajah, Kumaran; Leonard, David A.; Di, Luigi; Feingold, Randall S.; Israeli, Ron; Cetrulo, Curtis L.
<x xml:space="preserve">Abstract</x> Reconstruction of limb‐threatening lower extremity defects presents unique challenges. The selected method must provide adequate coverage of exposed bone, joints, and tendons while maximizing function of the limb. The traditional workhorse flaps, the free latissimus dorsi and rectus abdominis flaps, have been associated with donor site morbidity and bulkiness that can impair rehabilitation. We report a case series (n = 18) in which the free serratus anterior muscle flap and split thickness skin graft (STSG) was used for lower limb soft tissue coverage. Injuries were due to diabetes (9/18), trauma (7/18), and chronic venous stasis (2/18). A 94% flap survival rate was observed and all but one patient was ambulatory. No donor site morbidity was reported. Our series demonstrates that serratus anterior is an advantageous, reliable free flap with minimal donor site morbidity. © 2013 Wiley Periodicals, Inc. Microsurgery 34:183–187, 2014.